+0  
 
0
32
1
avatar

 

Solve for x: (3x + 12)(x + 4) = (4x^2 + 8x + 8x^2)/(2x).

 Nov 5, 2022
 #1
avatar+4 
0

\((3x+2)(x+4)=\frac{4x^2+8x+8x^2}{2x}\)
simplify

\(3x^2+24x+48=2x+4+4x\)

simplify

\(3x^2+24x+48=6x+4\)
subtract 6x+4

\(3x^2+18x+44=0\)
quadratic formula

\(\frac{-18 \pm \sqrt{18^2-4(3)(44)}}{2(3)}\)

After simplifying the quadratic formula, we get

\(-3\pm\frac{i\sqrt{194}}{6}\)
so that's our answer :)

 Nov 5, 2022
edited by Guest  Nov 5, 2022
edited by Guest  Nov 5, 2022

25 Online Users

avatar
avatar